Dark Matter: Peculiarities within the Li1−xRE5+xW8O32 series (RE = Dy − Lu) - Dorn, Katharina V.; Blaschkowski, Björn; Bamberger, Heiko; van Slageren, Joris; Widenmeyer, Marc; Weidenkaff, Anke; Suard, Emmanuelle; Hartenbach, Ingo (Journal of alloys and compounds, 2021)
•Mixed-valency of tungsten due to Li:RE ratio.•Determination of Li:RE ratio via X-ray and neutron diffraction.•Confirmation of W(V) thorough EPR measurements.•Raman spectroscopic and magnetic investigations of the title compounds. Single crystal and crystal structure of Li1−xHo5+xW8O32. [Display omitted] The derivatives of the Li1−xRE5+xW8O32 series (RE = Dy–Lu) all crystallize C-centered in the monoclinic system (a = 1897–1909 pm, b = 560–562 pm, c = 1127–1152 pm, β ≈ 111.1°, Z = 2). In the crystal structures of all representatives there are atomic positions, which show a mixed occupation of Li+ and the respective RE3+ cations. For RE = Dy this ratio is determined to be 1:1, resulting in space group C2/c. For RE = Ho–Lu, two crystallographically distinguishable positions exhibit the aforementioned mixed occupation with one of these being preferably occupied with Li+ and the other with RE3+ cations, causing the inversion symmetry to be lost, thus, their structure solution is best performed non-centrosymmetrically in space group C2. Furthermore, in the overall structure a deficiency of lithium with respect to the ideal formula LiRE5W8O32 was determined by both single crystal and neutron diffraction experiments and therefore the composition can be described better as Li1−xRE5+xW8O32. The resulting excess of positive charges in the formula is compensated by a partial reduction of the tungsten cations from their highest oxidation state, which is also indicated by the dark blue, almost black color of the compounds and was supported by magnetic susceptibility and electron paramagnetic resonance (EPR) measurements.